Effects of Folic Acid Intake during Pregnancy whose Mother was Exposed to Cigarette Smoke towards Brain Neurons Apoptosis Index and Quantity of Mice (Mus musculus) Offspring - Ningrum, Nyna Puspa; Joewono, Hermanto Tri; Widjiati, Widjiati (Folia Medica Indonesiana, 2018)
Folic acid contains 5-methyltetrahydrofolate (5-MTHF), one of antioxidants that can be used to inhibit reaction caused by cigarette smoke exposure. Folic acid is able to inhibit the levels of Reactive Oxygen Species (ROS) so as to reduce the occurrence of neuronal apoptosis. The objectives of this study was to determine the effect of folic acid intake during pregnancy whose mother was exposed to cigarette smoke on brain neurons apoptosis index and quantity of mice (Mus musculus) offspring. This study was an experimental laboratory study with posttest-only control group design. The subjects were 24 female mice divided into 4 groups consisting of one control group and three treatment groups. Sampling used simple random sampling, each group consisting of 6 animals. Control group 1 was not given treatment during pregnancy, group 2 was given with folic acid orally on days 0-17 of gestational age as much as 0.06 mg/day/mice. Group 3 was given with cigarette smoke exposure on days 7-17 of gestational age, amounting to 2 cigarettes/day. Group 4 was given with cigarette smoke exposure on days 7-17 of gestational age, amounting to 2 cigarettes/day and folic acid orally on days 0-17 of gestational age as much as 0.06 mg/day/mice. The result showed significant differences in all variables. In neurons apoptosis index, there were significant differences between groups 1 and 3, groups 2 and 3, groups 3 and 4, significant differences in the quantity of neurons between groups 1 and 3, groups 2 and 3, groups 2 and 4. The study concluded that there were significant difference in neural apoptosis index between all groups, and there were also significant differences in the quantity of neurons between all groups.